Pelayanan Prima Perawat Berdasarkan Persepsi Pasien di Ruang Rawat Inap Talaga Bodas (Penyakit Dalam Pria Kelas 3) Rumah Sakit Tingkat II 03.05.01 Dustira Cimahi 2019 - Lilis Rohayani; Iin Inayah; Anisa Shofiyani Shoumi; Andria Pragholapati (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
ABSTRACT Excellent service is the attitude or way of service providers who play a major role in creating satisfaction for patients, so the hospital's effort to improve the quality of service and patient satisfaction is to implement service excellence. Factors that must be applied by nurses in providing excellent service, including abilities, attitudes, appearance, attention, action and accountability. This study aims to determine the description of excellent service nurses based on patient perceptions in the Talaga Bodas inpatient (Class 3 Male Disease) Kindergarten II Hospital 03.05.01 Dustira Cimahi City in 2019. The study design was an analytic survey. The total sample of 149 respondents using purposive sampling technique with inclusion and exclusion criteria. Data collection was performed using a Likert scale questionnaire method. Analysis of data through two stages, namely univariate to see the frequency distribution. The results showed as many as 80 respondents (53.7%) felt excellent service. It is recommended that each inpatient room has a standard operating procedure standard (SOP) so that all nurses know the steps - good steps to perform excellent service to increase patient satisfaction. Keyword: Service Excellent, Nurse Hospital